PROJECT ACTIVITIES IN RUSSIAN LANGUAGE CLASSES - Komilova Mukarram Kobiljonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article discusses the use of the project method as a component of the education system. About the applications of various types of projects that allow solving different tasks in teaching and educating students. About project activities in Russian language lessons, which makes it possible to: - develop and improve students’ communicative competencies.